THREE DIMENSIONAL ANIMATION OF THE TRANS JOGJA BUS TOUR LINE USING PATH TECHNIQUE - Retnowati, Nurcahyani Dewi; Kusumaningrum, Anggraini; Fatimatuzzahroh, Fatimatuzzahroh (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2018)
Three-dimensional animation is widely used in various needs, one of its applications can be used as a medium for information on Trans Jogja bus tour line. This information media is useful for Trans Jogja bus users in knowing bus routes so that it is easier to use Jogja Trans buses. In the design of three-dimensional animation, the Trans Jogja bus route uses Paths techniques in the 3D Blender software and in making the application display using Construct 2 software. The design is then implemented in the form of animated videos. The 3D animation application of the Trans Jogja Bus route that is published on the itch.io site gets as many as 115 views and that downloads as many as 127.